TAXONOMIC COMPOSITION OF THE DENDROFLORA OF THE KUHISTAN BOTANICAL-GEOGRAPHICAL DISTRICT - Gulchehra Dadaeva (The Bioscan, 2024)
This article presents the results of studying the species composition of the dendroflora of the Kukhistan district. The features of the taxonomic composition are considered. As a result of the conducted research, the species composition of the dendroflora of the botanical-geographical Kukhistan district was formed for the first time, according to which it was established that it consists of 4292 herbarium specimens of 116 species belonging to 26 families and 46 genera. The 5 polymorphic families with the largest number of genera and species account for 66.37% of the total dendroflora. The results show that this dendroflora is characteristic of the Mountain-Central Asian province.